Mass Media and Eco-awareness of Bangladesh - Reza, Shishir (EAST WEST JOURNAL OF HUMANITIES, 2017)
Awareness edifice and dissemination plays deep-seated role from general public, local farmers, scientists, policy makers, planners and politician in the government. On the subject of the environment and development inconsistency, environmental wakefulness in the developing countries like Bangladesh is one of the current topics. Environmental awareness helps social groups and individuals to acquire familiarity and sensitivity about the total environment and its allied problems. As the general people of Bangladesh explores information of nature, environment and biodiversity through television, newspaper and radio -mass media can take part in a vital role to enlarge the apprehension about the challenges, problems, eco-friendly technologies, laws and policies and even development aspects of environment among them.